The jerk [videorecording (DVD)] - Martin, Steve, 1945-; Martin, Steve, 1945-; Gottlieb, Carl; Elias, Michael; Peters, Bernadette; Adams, Catlin; King, Mabel, 1932-1999; Ward, Richard, 1915-1979; Williams, Dick Anthony; Macy, Bill, 1922-2019; Walsh, M. Emmet, 1935-; O'Neill, Dick, 1928-1998; et al. (Universal, 2005)
A rags-to-riches-to-rags story. Navin Johnson, adopted son of a poor black sharecropper family, produces some crazy inventions that lead him from rags to riches and right back to rags.